Assessment of tumor response to chemotherapy in patients with breast cancer using 18F-FLT: a meta-analysis - Deng, Sheng-Ming; Zhang, Wei; Zhang, Bin; Wu, Yi-Wei (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
Purpose: To determine the diagnostic performance of 3'-deoxy-3'-18F-fluorothymidine positron emission tomography/computed tomography (FLT PET/CT) and FLT PET for evaluating response to chemotherapy in patients with breast cancer. Methods: Databases such as PubMed (MEDLINE included) and excerpta medica database (EMBASE), were searched for relevant original articles. The included studies were assessed for methodological quality with quality assessment of diagnosis accuracy studies (QUADAS) score tool. Histopathological analysis and/ or clinical and/or radiological follow-up for at least six months were used as the reference standard. The data were extracted by two reviewers independently to analyze the sensitivity, specificity, summary receiver operating characteristic (SROC) curve, area under the curve (AUC), and heterogeneity. Results: The present study analyzed a total of 4 selected articles. The pool sensitivity was 0.773 [95% confidence interval (CI): 0.594-0.900]. The pooled specificity was 0.685 (95% CI: 0.479-0.849) on basis of FEM. The pooled LR+, LR-, and DOR were 2.874 (1.492-5.538), 0.293 (0.146-0.589), and 14.891 (3.238- 68.475), respectively. The AUC was 0.8636 (±0.0655), and the Q* index was 0.7942 (±0.0636). Conclusions: Our results indicate that 18F-FLT PET/CT or PET is useful to predict chemotherapy response in breast cancer with reasonable sensitivity, specificity and DOR. However, future larger scale clinical trials will be needed to assess the regimen of 18F-FLT PET/CT or PET in monitoring the response to chemotherapy in breast cancer patients.